Potential Signatures and the Means of Detecting a Hypothetical Ground Source Cooled Nuclear Reactor. Issue 2 (3rd May 2016) - Kim, Lance K.; Jungwirth, Rainer; Renda, Guido; Wolfart, Erik; Cojazzi, Giacomo G. M.
ABSTRACT: This preliminary study considers the feasibility of cooling a small nuclear reactor (tens of megawatts thermal) with a well doublet that taps groundwater and injects heated fluid beneath the surface. The associated signatures differ substantially from those of conventional cooling systems. Instead of a plume of steam or outflows of heated water, only wellheads may be observed at a site without access to surface water. Other potential signatures include surface thermal anomalies, geomorphological alterations, induced seismicity, and altered groundwater chemistry. As these signatures may be faint and lag reactor operations, an understanding of the system's operating principles and telltales of hydrogeological conditions conducive to groundwater flow become more critical for detection of such reactor by remote sensing.